Head teachers Leadership Styles and Students’ Academic Performance in Selected Schools in The Ahafo-Ano South District in Ghana - Adangabe, Amos Amuribadek; Boateng, Benjamin (South Asian Journal of Social Sciences and Humanities, 2022)
The goal of this study was to see how the influence of School heads’ leadership styles on students’ academic achievement in a sample of chosen primary schools in the Ahafo-Ano South region. Three hundred and sixty-six (366) respondents completed a questionnaire, which comprised six (6) head teachers, twenty-four (24) instructors, and three hundred and thirty-six (336) students. The study found out that democratic and transformational leadership were the main styles of leadership that headteachers employed to ensure improvement in the academic performance of students as they gave room for followers (students and teachers) to express themselves and encouraged them to go beyond their self-interest and embrace the school’s established objectives. Again, the study found out that about 72 per cent of respondents explained that the leadership style of headteachers greatly influenced students’ academic performance. Democratic and transformational leadership styles were the main ones for improving students’ academic performance rather than autocratic leadership styles. To ensure effective and appropriate usage of leadership styles and practices in schools, the study recommends compulsory continuous professional development in leadership for headteachers by the Ghana Education Service; teachers should be able to assess and suggest the performance of headteachers in order to keep checks on them on a nearly daily basis; to become a Headteacher, training and other academic achievements should be considered and not only the length of service. Headteachers should identify teachers with potentials for effective and efficient school leadership training and mentorship in their respective schools.